Relacoes entre composicacorporal e desempenho anaeróbio em jovens futebolistas - de Sousa, S.; Rodrigues, E. Q.; Cintra Filho, D. A. (Revista Brasileira de Ciência e Movimento, 2013)
Body composition and anaerobic performance indices are important for soccer players considering that the soccer player needs good parameters of body composition (Muscle mass, Bone mass and Body fat) and your anaerobic performance must be effective because the action in a game of soccer is characteristic anaerobic such as sprint, jumps and direction change. The aim of this study was to investigate the correlation between body composition and anaerobic performance of young soccer players. This study present cross analytical characteristic and the sample (20 young soccer players) was chosen for convenience. Methods: 20 young soccer players (13.47 ± 0.12 years; 52.35 ± 4.14kg; 162.59 ± 16.59 cm) performed: 1) Analysis of body composition (Bone Densitometry - DEXA). Anaerobic performance: 2) Sprint 30 meters. 3) Sprint 60 meters. 4) Test Vertical Jumps with and without countermovement (VJWC and VJCM). Statistical analysis was through the Shapiro-Wilk test for checking normality (p <0.05), with the finding normality was performed correlations with the Pearson correlation test, with significance set at p <0.05, the Software Statistica 7 performed the analysis. Results: Altogether the body composition displayed correlations between 0.462 and 0.654, bone mass (full mass and lower limb) displayed the higher number of associations with anaerobic performance with values between 0.448 and 0.654 showed relationship with all anaerobic performance variables. Thus, we conclude that body composition is correlated with anaerobic performance variables and mainly bone mass. Thus, it seems that bone mass in young players is important for the performance in anaerobic activity soccer.